Continuous passive movement does not influence motor maps in healthy adults - McDonnell, Michelle N.; Hillier, Susan L.; Opie, George M.; Nowosilskyj, Matthew; Haberfield, Miranda; Todd, Gabrielle (Frontiers in Human Neuroscience, 2015)
Hand weakness following stroke is often associated with a reduced representation of the hand in the primary motor cortex. Meaningful sensory input can induce sensorimotor reorganisation in the brain, but the effect of continuous passive motion on the cortical representation is unknown. The purpose of this study was to determine whether repeated sessions of continuous passive movement (CPM) of the thumb induce a lasting increase in the motor cortical representation of a thumb muscle in healthy adults. Thirteen right-handed healthy adults (mean age 24.3 ± 4.3 yrs) participated in the study. Single-pulse Transcranial Magnetic Stimulation (TMS) was delivered over the motor area of the target muscle (abductor pollicis brevis) before and/or after a thirty minute session of thumb CPM administered on three consecutive days. TMS was also delivered five days after cessation of the CPM intervention. The response to TMS (motor evoked potential) was recorded in the target muscle with surface EMG. Resting motor threshold, motor evoked potential amplitude at a specified intensity, and the area and volume of the cortical representation of the target muscle were measured. Thumb CPM had no significant effect on TMS parameters (p > 0.05 all measures) and performance of an attention task remained unchanged within and across CPM sessions. The results suggest that three sessions of repetitive passive thumb movement is not sufficient to induce a change in the cortical representation of the thumb and is unlikely to reverse the decreased representation of the affected hand following stroke.